0757 Increasing Number of Cases Who Had Both Hypersomnolence Disorders and Developmental Disorders With Orexin Measurements. (27th May 2020) - Imanishi, A; Yoshizawa, K; Tsutsui, K; Omori, Y; Ono, T; Ito Uemura, S; Mishima, K; Kondo, H; Kanbayashi, T
Abstract: Introduction: Recently, attention has been paid to the relationship between developmental disorders such as attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD), and sleep disorders. We meet many developmental disorder patients who complaint hypersomnolence. Among these patients, cases with coexistence of central hypersomnia and developmental disorders, or developmental disorder alone were increased. Therefore, we first investigated patients with the complaint of hypersomnolence, who were also suspected developmental disorders. Furthermore, we have been measuring CSF orexin in 17 cases suspected of both disorders to investigate orexin levels of these patients. Methods: 86patients who complained of EDS with suspicion of developmental disorders had been examined. In order to diagnose hypersomnolence disorders, PSG and MSLT were performed. Psychological examinations were performed for diagnosing developmental disorders.We have been measuring for CSF orexin in 17 cases suspected both hypersomnolence and developmental disorders. We examined the onset of hypersomnolence and the clinical history of these ADHD or ASD cases for more details. Results: In 86 examined cases, developmental disorders coexisted in 30 cases. Among 30 cases, ADHD were 18, ASD were 6 and both diagnosed were 6 cases. Among them, 20 cases diagnosed as having coexistence of hypersomnia (8: narcolepsy, 12: IHS) and developmental disorders (ADHD:12, ASD:4, ADHD/ASD:4). In 17 cases with orexin measurements, 10 cases coexisted ADHD and 4 cases coexisted ASD. Two cases diagnosed as both ADHD and ASD. In 10 ADHD cases, 3 cases had low orexin levels, and 7 cases had normal orexin levels. Other 7 ASD cases had normal orexin levels. Conclusion: ADHD has a higher rate of central hypersomnia (12/18) compared with ASD and the rate of narcolepsy was also high (5/12). While patients in ASD was diagnosed as IHS (3/6), narcolepsy cases were not observed. It became clear that the majority of patients had developmental disorder or had a tendency for developmental disorder before the onset of hypersomnolence.Although it is possible that ADHD/ASD symptoms may be exacerbated by orexin dysfunctions, ADHD/ASD may not newly occur. There were cases with low orexin levels, but it seems that narcolepsy happened to coexist with developmental disorders. Support: a